Performance-Based Assessment for Learning in Middle Schools: Physical Education, Sports and Health - Irvan, Irvan (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study aims to evaluate the implementation of physical education, sports, and health education in public middle schools. This type of research is called qualitative research. The evaluation was conducted involving 20 PJOK teachers spread across various public middle schools in Makassar City. We used observation and in-depth interviews as data collection techniques. Observations were conducted to directly observe the learning process in the classroom, while interviews were conducted to explore information related to experiences, obstacles, and teachers' views on the implementation of PJOK learning. The collected data were analyzed using qualitative analysis techniques with the steps of data reduction, data presentation, and drawing conclusions/verification. The results of the study showed that, although most teachers had implemented PJOK learning well, several major obstacles were found, namely limited sports facilities and limited time for practicum implementation. Based on these findings, the study recommends the need to improve PJOK teacher training, improve sports facilities and infrastructure, and add time for practicum learning in order to improve the quality of PJOK learning in public middle schools in Makassar City.